PERPANJANG DAYA SIMPAN BUAH TOMAT (SOLANUM LYCOPERSICUM) DENGAN EDIBLE COATING BERBAHAN DASAR PATI SINGKONG (MANIHOT UTTILISIMA): PERPANJANG DAYA SIMPAN BUAH TOMAT (SOLANUM LYCOPERSICUM) DENGAN EDIBLE COATING BERBAHAN DASAR PATI SINGKONG (MANIHOT UTTILISIMA) - Sukarman Hadi Jaya Putra (Program Studi Biologi, Fakultas Matematika dan Ilmu Pengetahuan Alam, Universitas PGRI Banyuwangi, Jalan Ikan Tongkol No 01, Telp (0333) 421593, 428592 Banyuwangi 68416, 2022)
Tomato fruit that is harvested will retain its freshness for a maximum of 6-7 days, because during that time the fruit is still able to maintain metabolic activity by recycling the food reserves stored in the fruit. However, if it is more than that time, the quality of the fruit begins to decline, such as the fruit begins to wrinkle, is damaged and can even experience decay. Handling must be done immediately when the fruit is just harvested or before the fruit is 1 week old, so that the condition of the fruit can still be maintained. One way is to use an edible coating made from cassava starch. The content of tannins in cassava starch is able to kill bacteria. This study aims to test edible coatings made from cassava starch with different concentrations on the shelf life of fresh tomatoes. The research design used was descriptive quantitative in the form of a completely randomized design (CRD) with 3 different concentrations, namely 0%, 3%, and 6%. Each treatment consisted of 5 replications. Thus, 15 experimental units were obtained. The tomatoes used are tomatoes purchased at the market and are 7 days old after harvest. Soaking taro starch edible coating was carried out for 24 hours and stored in an open space at room temperature. Parameters observed were weight loss and tomato fruit morphology. The results showed that the use of edible coating with cassava starch as the base material had a significant effect (P<0.05) on the weight loss of tomatoes. The most optimal concentration of edible coating is 6% because it has a longer resistance level in extending the shelf life of tomatoes. Likewise, the morphology of tomatoes is better at a concentration of 6%. Fresh tomatoes stored with edible coating treatment made from cassava starch with a concentration of 6% were able to last up to 14 days at room temperature compared to other concentrations.